Pyelonephritis during pregnancy (opinion of the editor-in-chief about the problem) - M. I. Kogan (Вестник урологии, 2020)
The editorial board concludes the discussion on the problem of acute pyelonephritis in a pregnant woman. As editor-in-chief, I express my gratitude to the authors of publications on this subject [1–8]. At the same time, I want to draw attention to the weak activity of urologists in reaction to the discussion. In my opinion, one of the reasons for this is the lack of large-scale research on this issue in Russian Federation. Although, in the world, things are the same way for the most part. Therefore, it is extremely difficult in current medical practice to solve tactical tasks and make inferences in many clinical situations.I do not intend to comment in any way on the scientific publications of respected colleagues who spoke on the pages of the journal “Urology Herald”. Nevertheless, I want to give my considerations based solely on my own clinical experience in emergency urology and based on many scientific studies with my fellows in the Rostov-on-Don City Emergency Hospital and Rostov State Medical University.